Vestibular Migraine Confounds Management of Superior Canal Dehiscence Syndrome. Issue 7 (August 2022) - Smetak, Miriam R.; Cass, Nathan D.; Manzoor, Nauman F.; Hatton, Kelsey; Perkins, Elizabeth L.; Rivas, Alejandro; O'Malley, Matthew R.; Bennett, Marc L.; Haynes, David S.
Abstract : Objective: To investigate the prevalence of vestibular migraine (VM) in a cohort of patients with radiologic confirmation of superior canal dehiscence (SCD) and to compare management of superior canal dehiscence syndrome (SCDS) in patients with and without comorbid VM. Study Design: Retrospective review of a SCD database. Setting: University-based tertiary medical center. Patients: Ninety-one patients identified with SCD from 2009 to 2017. Interventions: None. Main Outcome Measures: Coincidence of VM and SCD, and resolution of symptoms. Results: Ninety-one patients with SCD met the inclusion and exclusion criteria. VM was diagnosed in 36 (39.6%) patients. Of those receiving medical therapy for VM alone, five (45.5%) reported symptom resolution, five (45.5%) reported partial improvement, one (9.1%) had no change, and none worsened. Fifteen patients (41.7%) were treated with both surgery (for SCD) and medical therapy (for VM). Seven (46.7%) reported symptom resolution, seven (46.7%) reported partial improvement, and one (6.7%) worsened. There was no statistically significant difference in symptom resolution between SCD + VM patients who were treated medically compared with those treated with medical therapy and surgery ( p = 0.951). There was no significant difference in symptom resolution after surgery between SCD + VM and SCD-only cohorts ( p = 0.286). Conclusions: This is the first study describing the incidence of VM in a cohort of patients with SCDS. The symptoms of VM confound those of SCDS and unrecognized or undertreated VM may contribute to surgical failure in SCDS. Therefore, we recommend a high index of suspicion for VM in patients with SCDS and a trial of medical therapy in the setting of suspected VM.